Occult Hepatitis B Infection in Kidney Transplant Patients - Paramita, Ida Ayu Pradnya; Wibawa, I Dewa Nyoman (The Indonesian Society for Digestive Endoscopy, 2022)
Occult hepatitis B infection (OBI) is still a topic of debate worldwide. It is defined as the presence of hepatitis B virus (HBV) DNA in serum and/or liver from HBsAg-negative subjects. OBI may lead to the development of cirrhosis and hepatocellular carcinoma. It continues to present several unique challenges in organ transplantation despite the availability of an effective vaccine to prevent HBV infection and the introduction of oral therapy to treat HBV infection. HBV reactivation following organ transplantation can occur even in recipients with absent hepatitis B surface antigen and remains an important cause of morbidity and mortality. Concerning OBI complications, the screening of HBV DNA by the highly sensitive molecular means should be implemented for both recipients of organ transplant and organ transplant donors especially in highly endemic areas of HBV. In the era of potent antivirals and with evolving knowledge, HBsAg (+) renal transplant candidates and recipients can be monitored and successfully treated. Kidney organs from HBsAg-negative and anti-HBc–positive donors should be considered for transplant candidates after weighing the risk-benefit ratio. All transplant candidates should receive HBV vaccination if they are not immune to facilitate receipt of an organ from a donor with anti-HBc seropositivity.